An overview on marine anti-allergic active substances for alleviating food-induced allergy. Issue 15 (21st August 2020) - Wang, Kexin; Pramod, Siddanakoppalu Narayana; Pavase, Tushar Ramesh; Ahmed, Ishfaq; Lin, Hang; Liu, Liangyu; Tian, Shenglan; Lin, Hong; Li, Zhenxing
Abstract: Food provides energy and various nutrients and is the most important substance for the survival of living beings. However, for allergic people, certain foods cause strong reactions, and sometimes even cause shock or death. Food allergy has been recognized by the World Health Organization (WHO) as a major global food safety issue which affect the quality of life of nearly 5% of adults and 8% of children, and the incidence continues to rise but there is no effective cure. Drug alleviation methods for food allergies often have shortcomings such as side effects, poor safety, and high cost. At present, domestic and foreign scientists have turned to research and develop various new, safe and efficient natural sources of hypoallergenic or anti-allergic drugs or foods. There are many kinds of anti-allergic substances obtained from the plants and animals have been reported. Besides, probiotics and bifidobacteria also have certain anti-allergic effects. Of all the sources of anti-allergic substances, the ocean is rich in effective active substances due to its remarkable biodiversity and extremely complex living environment, and plays a huge role in the field of anti-food allergy. In this paper, the anti-food allergic bioactive substances isolated from marine organisms encompassing marine microbial, plant, animal sources and their mechanism were reviewed and the possible targets of anti-allergic substances exerting effects are illustrated by drawing. In addition, the development prospects of marine anti-allergic market are discussed and forecasted, which can provide reference for future research on anti-allergic substances.